Estrutura da inflaç\~ao brasileira: Determinantes e desagregaç\~ao do IPCA - Thiago Sevilhano Martinez; Vinícius dos Santos Cerqueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper aims to discuss the determinants of Brazilian inflation measured by the Extended National Consumer Price Index (IPCA) from 2000 to 2009. We built 22 disaggregated series, the segments classification, crossing the classification in tradeables/non-tradeables/monitored prices with the main groups of the IPCA (food and beverages, housing, household goods, clothing, transportation, health and personal care, personal expenses, education and communication). Segments with more influence on inflation are ordered by the so-called Inflation Targeting Pressure Index (ITPI), designed to measure the impact of each prices group on the IPCA. The paper also presents the results of an econometric model using the transfer function method, with monthly data from 1999 to 2009 to estimate the macroeconomic determinants of inflation in the 22 disaggregated series. The determinants of most influential segments are explored following the results of the econometric model. Finally, it discusses the implications for inflation policies.
Keywords: E31; 330; Inflation; Verbraucherpreisindex; Brasilien